Uric acid level in Chronic Kidney Disease patients and its association with other established CKD risk factors - Kumar Sah, Dilip; Shah, Shweta; Gurung, Alina (Birat Journal of Health Sciences, 2024)
Introduction: Chronic Kidney Disease (CKD) is a rising global health concern with increased cardiovascular risks. Hyperuricemia, linked to CKD and related conditions, warrants investigation. Objectives: This study examines the uric acid in different stages of CKD and the association between uric acid levels and established CKD risk factors. Methodology: A hospital-based prospective cross-sectional study was conducted at Birat Medical College Teaching Hospital from 10 June 2023 to 30 August 2023. We enrolled 90 patients with non-dialytic chronic kidney disease (CKD) by complete enumeration sampling method. Ethical approval was obtained from the institutional review committee of the college. Written informed consent was obtained from each participant. Data was collected by means of a self developed questionnaire. Blood samples were obtained for estimation of serum creatinine and uric acid level and recorded in Microsoft excel sheet and analyzed by using SPSS software version 23. Results: Hyperuricemia was seen in 33(36.7%) ranging from 3.5-12 mg/dl with an average uric acid level of 6.38 mg/dl and a standard deviation of 1.43 mg/dl of total 90 patients. The mean serum uric acid level was highest in stage 2 CKD which includes 6.88±2.10 ranging from 4.3-12 mg/dl. CKD patients with a history of alcohol intake had increased risk of hyperuricemia and it was statistically significant (p value 0.005). Different stages of CKD (p value: 0.70), age groups, (p value 0.17), gender(P value 0.082), diabetes(p value 0.954), hypertension(p value 0.364), other CVDs(p value 0.649)and anemia(p value 0.0602)had no statistical significant association with hyperuricemia. Conclusion: In conclusion, hyperuricemia prevalence was observed in CKD patients, with the highest levels in stage 2 CKD. Notably, alcohol intake significantly correlated with hyperuricemia, while other studied factors did not show significant associations.